INTEGRATION OF MULTIPLATFORM DESKTOP, WEB AND MOBILE APPLICATIONS AT PT. PRIMA ARTHA KREASINDO USING WEB SERVICE - Wijaya, Ardie Halim; Hermanto, Wiyono (ISTEK WIDURI, 2022)
The research entitled “Integration of Multi-Platform Desktop, Web and Mobile Applications at PT. Prima Artha Kreasindo Using Web Service” aims to integrate several desktop, web and mobile-based application systems into one application system using web services to make it more practical, effective and efficient. The developed application system can be installed on computers, laptops and cellular phones. The research was conducted by coding an integrated application program with a web service link facility and simulating the operation of the application. The use of the right device makes the system run more effectively and efficiently. The results showed that the multi-platform application program can be applied at PT. Prima Artha Kreasindo on the sales application system, with a point of sale system (POS, point of sales) and inventory control in the warehouse. The sales application program at the company became more practical, effective and efficient.